Effects of HD-tDCS combined with Bosu ball training on static and dynamic postural stability among individuals with chronic ankle instability - Ge, Yubin; Gao, He; Huang, Xueke; Luo, Xin; Liu, Yanhao; Wang, Dongmei; Shen, Peixin; Guo, Liang; Song, Qipeng (Frontiers in Sports and Active Living, 2025)
PurposeChronic ankle instability (CAI) is characterized by a combination of peripheral dysfunction and maladaptive neuroplasticity in central nervous system, leading to persistent postural stability deficits. This study aims to investigate the effects of high-definition transcranial direct current stimulation (HD-tDCS) combined with Bosu ball training (BBT) on the static and dynamic postural stability in individuals with CAI.MethodsA total of forty participants were randomized to receive either HD-tDCS + BBT (n = 20) or BBT (n = 20) interventions, delivered over six weeks with three 20-minute sessions per week. Static and dynamic postural stability was assessed pre- and post-intervention via single-leg stance and drop landing tests, with kinetic data captured by a force platform (1,000 Hz). Data were analyzed using two-way mixed-design ANOVA.ResultsSignificant group-by-time interactions were detected in the center of pressure-root mean square (CoP_RMS) during single-leg stance (p = 0.036, η2ₚ = 0.134) and the time to stabilization (TTS) during drop landing (p = 0.007, η2ₚ = 0.209) in the mediolateral (ML) direction. Post hoc comparisons showed that the both of them were decreased after intervention, and greater decreases were observed by the intervention of HD-tDCS + BBT compared to BBT. And, a significant time main effect was observed in the CoP_RMS (p < 0.001, η2ₚ = 0.382) and the TTS (p = 0.005, η2ₚ = 0.224) in the anteroposterior direction, they both decreased after HD-tDCS + BBT and BBT interventions.ConclusionsBoth BBT alone and the combined HD-tDCS + BBT interventions enhanced static and dynamic postural stability in individuals with CAI, while the combined HD-tDCS + BBT intervention demonstrated significantly greater efficacy in improving postural stability in the ML direction compared to BBT alone.